2018
DOI: 10.1186/s12876-018-0775-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits and Helicobacter pylori infection: a cross sectional study at a Lebanese hospital

Abstract: BackgroundTo examine the association between dietary habits and Helicobacter pylori (H. pylori) infection among patients at a tertiary healthcare center in Lebanon.MethodsThis cross-sectional study was conducted on 294 patients in 2016, at a hospital in Northern Lebanon. Participants were interviewed using a structured questionnaire to collect information on socio-demographic and lifestyle characteristics; dietary habits were ascertained via a short food frequency questionnaire (FFQ). H. pylori status (positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 48 publications
8
31
0
2
Order By: Relevance
“…Similar data were also reported for raw cow milk samples in Japan (Fujimura et al 2002), as well as in Greeks (Angelidis et al 2011) and American (Dore et al 2001) herds. Supporting these data, a recent study reports a higher prevalence of H. pylori positively associated with the consumption of milk (Assaad et al 2018).…”
Section: 2a Foodsupporting
confidence: 53%
“…Similar data were also reported for raw cow milk samples in Japan (Fujimura et al 2002), as well as in Greeks (Angelidis et al 2011) and American (Dore et al 2001) herds. Supporting these data, a recent study reports a higher prevalence of H. pylori positively associated with the consumption of milk (Assaad et al 2018).…”
Section: 2a Foodsupporting
confidence: 53%
“…However, a number of other studies, including one conducted in Lebanon, found no such association, attributing the other positive findings to a birth cohort effect. Our results showed no association between gender and H. pylori detection rates, which is consistent with most of the literature, including local data 15 26–28…”
Section: Discussionsupporting
confidence: 92%
“…A systemic review presented a prevalence varying between 22% and 87.6% in the Eastern Mediterranean region 14. Regarding the investigations done in Lebanon, one study found the prevalence to be 52.4% on histology at a peripheral hospital in north Lebanon 15. The variation of results between our study and the aforementioned study could be due to the fact that it was conducted in a relatively peripheral hospital whereas our study was conducted in a central hospital (north Lebanon vs Beirut).…”
Section: Discussionmentioning
confidence: 99%
“…Our search identified 182 related references, of which 10 papers met our inclusion criteria . The flowchart describing the process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%